The Clergy during the Fourth Crusade as Portrayed in Geoffrey de Villehardouin’s Chronicle - Pentek, Zdzisław (Studia Ceranea, 2023)
An article analysing information about the clerics during the Fourth Crusade mentioned by the chronicler of this expedition, Geoffrey of Villehardouin († c. 1219), in the Old French chronicle La conquête de Constantinople. The author has distinguished three types of clerics, participants in the crusade, and traced mentions thereof in the work and the opinions about them.